2007
DOI: 10.1016/j.jallcom.2006.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Observation of hydrogen absorption/desorption reaction processes in Li–Mg–N–H system by in-situ X-ray diffractmetry

Abstract: The in-situ XRD measurements on dehydrogenation/rehydrogenation of the Li-Mg-N-H system were performed in this work. The ballmilled mixture of 8LiH and 3Mg(NH 2 ) 2 as a hydrogenated phase gradually changed into Li 2 NH as a dehydrogenated phase during heat-treatment at 200 • C in vacuum for 50 h. Neither Mg-related phases nor other intermediate phases were recognized in the dehydrogenated phase. With respect to the hydrogenation process, the dehydrogenated state gradually returned to the mixed phase of the Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Therefore, the reaction enthalpies for eq. (1) are 60.3 kJ/mol, and this agrees well with the experimental result of 44.1 kJ/mol [20] . All the results were calculated at zero absolute temperature and the Zero-point energy corrections were not taken into account any of the formation enthalpies in this study.…”
Section: Heat Of Formationsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the reaction enthalpies for eq. (1) are 60.3 kJ/mol, and this agrees well with the experimental result of 44.1 kJ/mol [20] . All the results were calculated at zero absolute temperature and the Zero-point energy corrections were not taken into account any of the formation enthalpies in this study.…”
Section: Heat Of Formationsupporting
confidence: 91%
“…that the temperature to desorb hydrogen at 1.0 bar equilibrium pressure is 90℃ [20] , which is close to the practical usage temperature of the proton exchange membrane fuel cell. Another 3Mg(NH 2 ) 2 +8LiH system has higher temperature for hydrogen desorption in order to obtain the products of magnesium nitride [14] , but this system still focuses on its higher H content and could be applied under the condition of higher temperature.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Both reactions probably contain more than two steps with formation of intermediate phases. From in situ PXD data Nakagawa et al reported that dehydrogenation reaction of 3Mg(NH 2 ) 2 with 8LiH under vacuum formed Li 2 NH around 200 • C, but no phase containing Mg was observed in the diffraction pattern [16]. Leng et al reported that the same reaction had 4Li 2 NH + Mg 3 N 2 as the end product above 400 • C [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…The numerous researches have been reported as to the reversible reaction mechanism of the Li-Mg-N-H system [12][13][14][15][16]. Especially, as for the intermediate phases during the reaction process, in situ measurement of structural change [17][18][19][20][21], theoretical calculation [22,23] and thermal stability [24] have been advanced. However, the reversible reaction mechanism under hydrogen pressure has not been sufficiently clarified, yet.…”
Section: Introductionmentioning
confidence: 99%